Nanoformulation-Based Drug Delivery of Phytoconstituents for Targeted Cancer Therapy: A Pharmaceutical Approach to Enhance Bioavailability and Therapeutic Index - Zanke, Ashwini A; Gaikwad, Kiran P; Jaiswal, Chaitali P; Ghait, Vikas N; Titare, Ananta G; maskar, Ankush K (Journal of Neonatal Surgery, 2025)
Background: While phytochemicals are known for their anticancer potential, their clinical impact is limited due to poor bioavailability and inadequate targeting. Utilizing nanoformulation-based delivery systems has emerged as a promising strategy to address these shortcomings and improve the overall therapeutic performance of plant-derived compounds. Methods: A systematic review was conducted by analyzing literature from 2012 to 2024 using PubMed, Scopus, and ScienceDirect. The studies included focused on nanoparticle-mediated delivery of phytoconstituents for cancer treatment, evaluating aspects such as bioavailability, targeting precision, cytotoxicity, and therapeutic success. Results: Among the 38 relevant studies, delivery systems such as liposomes, polymeric and solid lipid nanoparticles, and nanoemulsions were reviewed. Nanoformulations of phytochemicals like curcumin, quercetin, and resveratrol showed 3–10-fold improvement in cellular absorption and preferential tumor site accumulation. Liposomal curcumin notably achieved up to 80% tumor inhibition in mouse models. Polymeric carriers provided prolonged circulation and minimized side effects. Overall, these formulations boosted bioavailability by around five times and significantly enhanced therapeutic indices. Conclusion: Nanotechnology-enhanced delivery offers an effective route to improve the performance of plant-based agents in oncology. However, advancing these therapies into clinical settings requires more rigorous trials and regulatory harmonization.